Corporate Governance in Family Firms - Atmaja, Lukas Setia (International Research Journal of Business Studies, 2008)
This paper reviews the theoretical and empirical literature on the corporate governance in family controlled firms. In particular, it discusses conflicts of interest between owner and manager (referred to as Agency Problem I) as well as between minority and large shareholders (referred to as Agency Problem II) among family firms under agency theory framework. It is widely believed that families are better monitors of managers than other types of large shareholders, suggesting that Agency Problem I are less prevalent in family than in non-family firms. On the other hand, it is also argued that controlling families may extract private benefits at the expense of minority shareholders. In addition, the governance literature indicates that several conventional governance tools for controlling Agency Problem are less effective in dealing with Agency Problem II. This implies that other internally determined governance mechanisms such as boards of directors may play a more significant and effective role in controlling Agency Problem II in family firms.